TINJAUAN HUKUM ISLAM TERHADAP PERCERAIAN DENGAN ALASAN EKONOMI DAN KEKERASAN DALAM RUMAH TANGGA (Studi Kasus Di Pengadilan Agama Kota Malang 2019) - Haijan Haijan; Ahmad Subekti; Dwi Ari Kurniawati (Jurnal Hikmatina, 2020)
According to the 1slamic law, the principle of divorce is preceded by certain causes of the husband of the wife  , this is in accordance with the opinion of imam  Hanafi  in his book usul   fiqih, that is, 1slamic law always follows its gods whether there are gods or gods. So what   if there is a god  , then the action isdemanded so that in accordance with  whatis desired, then if according to the rules of divorce can be punished.  Divorce is a fact that occurs between married cuples, due to differences in principles  that can not be united again through the way of life. Each retains its own will and desire.  Without trying to budge for the achievement of family  intergrity.  Unwillingness and inability to acknowledge the shortcomings of oneslf and  or others a trivial problem to become large so that it ends in divorce Keywords: divorce economic reasons and violence